(untitled) (Journal of Shaheed Suhrawardy Medical College, 2026)
Background: As the worldwide burden of gynaecological malignancy continues to rise, early detection strategies focused on women with postmenopausal bleeding (PMB), have the potential to identify genital malignancies at an early treatable stage. Objective: The objective of this study is to investigate the association of PMB and its clinicopathological risk factors with the prevalence of gynaecoloical malignancies. Material and methods: This is a prospective cross-sectional study for a period of 1 year over 100 women with PMB. Results: Benign lesions are accounted for 71% of the cases of PMB and malignant lesions are for 29% cases. Endometrial polyps are the most frequent cause (22%) followed by cervical malignancy (17%), Leiomyoma (14%), Endometrial atrophy (13%), Endometrial malignancy (10%), Endocervical polyp (8%), Endometrial hyperplasia (5%), Endometritis with pyometra (4%) and Ovarian malignancy (2%). Among the malignancies, Cervical carcinoma (58.62%) is the commonest malignancy followed by endometrial carcinoma (34.48%) and ovarian carcinoma (6.89%). Endometrial cancer shows a significant association with increasing age (p = 0.008). On the other hand, Cervical Cancer exhibits significant association with lower socioeconomic status (p = 0.001), higher parity (5 and above) (p = 0.029), normal body weight categories (p = 0.007) and decreased ET up to 4 mm (p = 0.019). Endometrial Polyps and Endometrial Cancer have significant associations with increased ET (Endometrial Thickness), with p-values 0.016 and 0.007, respectively. On comparison between Benign and Malignant group, clear span is significantly greater in the Malignant group (p = 0.022). So, evaluation of risk factors of PMB in our study has showed significant association of Malignancies with increasing age, BMI, socioeconomic status, parity, clear span and endometrial thickness (ET). Conclusion: Our study represents an important and timely evaluation of the risk with the prevalence rate and pattern of gynaecological malignancies in women with PMB in our country. J Shaheed Suhrawardy Med Coll 2024; 16(2): 36-42